Involvement of adenosine A1 receptor in the sleep-promoting effect of fermented Perilla frutescens - Joy Bormate, Katrina; Kyung Lee, Bo; Kim, Tae Ho; James Perez Custodio, Raly; Hoon Cheong, Jae; Jin Kim, Hee; Hee Shim, Sang; Bang Pil, Gam; Jun Kim, Hyun; Ho Son, Rak; Hum Yeon, Sung; Wook Park, Jin; et al. (Journal of Functional Foods, 2024)
Perilla frutescens (PF) is a plant with various biological activities, including antioxidant and antidepressant activities; however, the efficacy of its fermented product has not been evaluated. Herein, we found that the Bacillus subtilis-fermented PF (FPF) increased non-rapid eye movement sleep and slow wave activity. FPF improved the sleep onset latency and sleep duration in a pentobarbital-induced sleep model, and this efficacy was abolished by the adenosine A1 receptor (A1R) antagonist. In addition, FPF increased and decreased the neuronal activity in sleep-activating and inhibiting brain regions, respectively, and these effects were also blocked by A1R antagonist 8-cyclopentyl-1,3-dipropylxanthine. Furthermore, FPF exhibited direct binding and agonistic activities for A1R. HPLC/NMR analysis revealed uracil, protocatechuic acid, apigenin-7-O-diglucuronide, and luteolin-7-O-glucuronide to be the major active components responsible for the sleep-promoting efficacy of FPF. In conclusion, this study suggests that FPF has A1R agonistic activity and this novel activity may be critical for its sleep-promoting effect.
Keywords: Adenosine A1 receptor; Fermented Perilla frutescens; Sleep disturbance; Sleep quality; Sleep-promoting effect